Higher insulin detemir doses are required for the similar glycemic control: comparison of insulin detemir and glargine in children with type 1 diabetes mellitus - BEREKET, ABDULLAH; HALİLOĞLU, BELMA; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (WILEY, 2015)
ObjectiveWe aimed to compare hemoglobin A1c (HbA1c), total and basal insulin doses, basal insulin injection frequencies, and body mass index (BMI) in children with type 1 diabetes mellitus (T1DM) who are receiving detemir and glargine as basal insulin in a basal-bolus therapy. MethodThis retrospective study included 117 (53 females) children and adolescents with T1DM older than 4 yr of age, minimum diabetes duration of 2 yr, and receiving basal-bolus insulin regimen (at least 4 injections/d, insulin aspart or lispro as bolus insulin). Comparisons were made for those receiving insulin detemir (n = 32) or glargine (n = 85) as the basal insulin. ResultsAge, pubertal status, BMI standard deviation scores, and diabetes duration were similar in detemir and glargine groups. Glycemic control was similar in both groups (HbA1c levels 8.9 2.1% vs. 8.5 +/- 1.7% for detemir and glargine, respectively; p = 0.497). Both mean basal insulin (0.52 vs. 0.41 U/kg/d, p < 0.001) and mean total daily insulin (1.11 vs. 0.93 U/kg/d, p < 0.001) doses were higher in the detemir group. Furthermore, higher ratio of twice-daily basal insulin injection was detected in the detemir group (62.5 vs. 32.9% p = 0.004). Subgroup analysis according to pubertal status, or the number of daily basal injections showed similar results. Conclusion Insulin detemir provides similar glycemic control with glargine, but, approximately 27% higher mean basal and 19% higher mean total insulin doses with two-fold more twice-daily basal insulin injection requirement.
Keywords: children; detemir; glargine; HbA1c; T1D; TREAT-TO-TARGET; PHARMACOKINETIC PROPERTIES; ANALOGS DETEMIR; STEADY-STATE; DOUBLE-BLIND; NPH INSULIN; LONG; ADOLESCENTS; VARIABILITY; PROFILE